Digital Transformation of Islamic Boarding School Financial System; Formulation, Implementation and Evaluation - Wardi, Moh.; Lidia Candra Sari; Supandi; Ismail; Moh Zainol Kamal; Hodairiyah; Irawati, Sri (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
The purpose of this study is to investigate the design, implementation and evaluation of the digitalization of the financial system at Al-Amin Prenduan Islamic boarding school in Sumenep. The data were gathered from key informants i.e. the Board of Kyais, finance officers, students, and their parents, using a qualitative descriptive approach. Secondary data came from institutional documents. The findings show that the Kyai Council was consulted during the development of the digital financial system, which took into account both payment and economic needs. The transformation included the development from the Pondok Payment Application (APIP) to the Al-Amien Financial System (AFS). Implementation involved cashless transactions via interbank transfers, facility provision in each unit, and financial restrictions on students' daily allowances. Santri’s parents also participate in monitoring through the Student Information and Administration Systems. The evaluation process includes regular meetings by the financial supervision team and field studies to enhance technological efficiency and adaptation.